Mental and physiological wellbeing while rowing across the North Atlantic: a single-case study of subjective versus objective data - Zeiner, Klaus; Dabiri, Babak; Burns, Ciara; Kummer, Lena; Kaniusas, Eugenijus (Frontiers in Physiology, 2023)
Unassisted rowing across the Atlantic Ocean is an extreme undertaking challenging the human body in every possible way. The reported rowing journey lasted for 42 days in a small vessel with 12 rowers, each rowing for 12 hours a day, broken into 3 hour shifts. This schedule disrupts the natural circadian cycle and autonomic balance, affecting subjective and objective wellbeing and sleep quality, that lack continuous empirical quantification.With a self-reported questionnaire and objective heart rate variability measurements every second day in a single female rower, we monitor evolutions of the subjective sleep quality and mental wellbeing as well as autonomic body control over the journey duration. We evaluate the hypothesis that extreme rowing impairs subjective and objective data in a similar way over time and that 3 hour shifts diminish the circadian rhythm of the autonomic body control.The sleep quality was mainly influenced by wake ups during sleep, while mental wellbeing was predominantly influenced by physical exhaustion. The perceived sleep quality and wellbeing dropped 2-3 days after the start with the rower not yet accommodated, in the middle of the journey with major wake ups, and again 5-6 days prior to the end with major exhaustion of the participant. Evolutions of the subjective perceptions diverge from that of the heart rate variability. The body's autonomic recovery during short sleep periods progressively decreases over the journey duration while the vagal activity rises and the sympathovagal balance shifts towards vagal tone. The shifts of 3 hours weaken the circadian rhythm of the heart rate variability.Our results demonstrate how human body meets extreme mental and physical exhaustion on the high seas. The gained physiological and psychological insights also offer a basis for effective preparation of undertakings involving extreme physical exhaustion and sleep deprivation.